Comparison of the key kinematic parameters of difficult handspring and tsukahara vaults performed by elite male gymnasts - Farana, R.; Uchytil, J.; Jandacka, D.; Zahradnik, D.; Vaverka, F. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The current study compared the key kinematic parameters of two difficult groups of vaults performed by elite male gymnasts. Five top-level male gymnasts (n=5) who participated in the 2010 World Cup competition performed Handspring and Tsukahara vault groups graded 6.2 points. For the 3D spatial movement analysis, we used two digital camcorders with a frame rate of 50 Hz. The data was digitized by the SIMI MOTION software. Temporal, spatial, velocity and angular variables were measured in critical phases of a vault. To establish the differences between the means, the effect size (ES) was calculated. Although both vaults have the same initial evaluation, the Handspring group requires highest peak, longer horizontal displacement of CoG and longer duration of the second flight phase and can be, in terms of performance, considered difficult.